Influence of Gesture and Linguistic Experience on Sign Perception. (24th August 2019) - Gimeno-Martínez, Marc; Costa, Albert; Baus, Cristina
Abstract: In the past years, there has been a significant increase in the number of people learning sign languages. For hearing second language (L2) signers, acquiring a sign language involves acquiring a new language in a different modality. Exploring how L2 sign perception is accomplished and how newly learned categories are created is the aim of the present study. In particular, we investigated handshape perception by means of two tasks, identification and discrimination. In two experiments, we compared groups of hearing L2 signers and groups with different knowledge of sign language. Experiment 1 explored three groups of children—hearing L2 signers, deaf signers, and hearing nonsigners. All groups obtained similar results in both identification and discrimination tasks regardless of sign language experience. In Experiment 2, two groups of adults—Catalan sign language learners (LSC) and nonsigners—perceived handshapes that could be permissible (either as a sign or as a gesture) or not. Both groups obtained similar results in both tasks and performed significantly different perceiving handshapes depending on their permissibility. The results obtained here suggest that sign language experience is not a determinant factor in handshape perception and support other hypotheses considering gesture experience.